Fast Adaptive Active Noise Control Based on Modified Model-Agnostic Meta-Learning Algorithm - Shi, Dongyuan; Gan, Woon-Seng; Lam, Bhan; Ooi, Kenneth (IEEE signal processing letters, 2021)
With the advent of efficient low-cost processors and electroacoustic components, there is renewed interest in the practical implementation of active noise control (ANC). However, the slow convergence of conventional adaptive algorithms deployed in ANC restricts its handling of typical amplitude-varying noise. Hence, we proposed a modified model-agnostic, meta-learning (MAML) strategy to obtain an initial control filter, which accelerates an adaptive algorithm's convergence when dealing with different types of amplitude-varying low-frequency noise. Numerical simulations with measured paths and real noise sources demonstrate its convergence acceleration efficacy in practical scenarios.